Development of IMS Network Structure and Vector Models Integrated with Mobile Communication Networks - Mammadov, F.H.; Orujova, M.Y. (Herald of Azerbaijan Engineering Academy, 2024)
The analysis of the IMS network was carried out, its main features, characteristics and advantages were noted, the three-level structure containing the service level, management level, as well as mobile communication networks and their interaction levels and its vector models were developed in this network.